Use of Cottonseed Meal in Feeding Yellow-Feathered Broilers: Effects on Performance Parameters, Digestibility and Meat Quality - Xiaohang Nie; Xiahan Wei; Weidong Niu; Fengming Li; Jiang Yuan; Gang Lv; Yong Chen; Jiancheng Liu (Veterinary Sciences)
This study investigated the effects of replacing soybean meal (SBM) with high-protein cottonseed meal (CSM) and de-phenolized cottonseed meal (DPCSM) on growth performance, apparent nutrient digestibility, serum biochemical parameters, slaughter traits, and meat quality in yellow-feathered broilers. A total of 5760 one-day-old male Liangfeng Hua broilers were randomly divided into five groups with eight replicates per group. The control group was fed a corn-SBM diet (SBM group), while the CSM50, CSM100, DPCSM50, and DPCSM100 groups replaced 50% and 100% of the equivalent protein from SBM with CSM and DPCSM, respectively. Compared to the control group, the CSM50 and DPCSM50 groups showed no significant negative effect on growth performance; however, dietary calcium digestibility was significantly reduced on day 21. Furthermore, CSM100 and DPCSM100 adversely impacted growth performance, significantly reducing crude fat digestibility and increasing serum urea nitrogen levels on day 42. The broilers in these groups also had reduced pre- and post-slaughter body weights, while those in the CSM50 and DPCSM100 groups exhibited decreased half-clearance rates. In addition, the CSM100 group had significantly increased pectoral muscle drip loss and a* (24 h) values. pH values measured at 45 min and 24 h were significantly elevated in the DPCSM50 and DPCSM100 groups. In conclusion, the replacement of SBM with CSM and DPCSM in yellow-feathered broiler diets should be limited to 50%.